Performance Evaluation of Financial and Economic Mechanisms of the State Stimulation of Innovative Activity in Russia - N. M. Abdikeev (Финансы: теория и практика, 2018)
The paper analyzes the effectiveness of budget fnancing of innovative activities in Russia. The structure of sources of fnancing of internal expenditures on research and development, branch orientation of the state support of innovative activity is considered. The estimation of the cost-effectiveness of technological innovation is given. The analysis is based mainly on the materials of Rosstat for 2013–2016. In addition, the authors cited international comparisons of innovative activity for 2012–2014. To assess the effectiveness of government measures to support innovation activity proposed “Golden rule of the economy.” It consists in determining the ratio of the main components of innovation activity (innovative goods and technologies) and the resources used, including budget fnancing. An important conclusion is made about the ineffcient mechanism of state support of innovative activity in Russia. Proposals for its improvement are formulated, including: bringing the content and structure of state programs in line with the objectives of the formation of conditions for accelerated technological modernization of the industry; introduction of the Institute of state programs of the mechanism of project fnancing and methods of the digital economy; reducing the number of targets of state programs; stimulating by an order of magnitude more technological costs carried out by industrial companies using the mechanism of public-private partnership; preferential state stimulation of process and organizational and managerial innovations in the creation of value chains; encouragement of own and commissioned research and development carried out by domestic companies; promotion of innovative activity in large industrial enterprises, etc.